ANALISIS POTENSI LESTARI PERIKANAN TANGKAP DI KOTA DUMAI - Hazmi Arief; Novia Dewi; Jumatri Yusri (Indonesian Journal of Agricultural Economics, 2014)
The purpose of this study was to know of the potential for sustainable of capture fisheries. This research background is decreasing of capture fisheries in Dumai for a few years. This research used primary and secondary data.. While the methods used in this study is a quantitatif analysis of potential for sustainable fisheries resources, Schaefer model technique CYP. According to bioeconomy analysis of three products fisheries resources ( shrimp, fish source, lomek ), the utilization of fishery resources in Dumai, especially shrimp was still below the optimal point and belongs to flagship poduct.The result of research showed that the optimal catches based on the result various fisheries management regimes that is:Maximum Economic Yield (MEY) of shrimp 125.483,70 tons, biang fish 1.740,82 tons, and lomek fish 77.664,16 tons. Maximum Sustainable Yield (MSY) of shrimp 34.901,39 tons, biang fish 117,18 tons, and lomek fish 461,10 tons